Grazing and neighborhood interactions limit woody encroachment in wet subtropical savannas - Macias, Daniel; Mazía, Noemí; Jacobo, Elizabeth Juliana (2018)
Woody encroachment in savannas is a worldwide concern, and there is growing consensus that anthropogenic activities play a central role in changing tree – grass interactions. We evaluated the influence of livestock grazing and neighborhood interactions on seedling emergence and survival of the native tree Acacia caven in wet savannas of northeastern Argentina. We hypothesized that grazing and grass competition act as biotic barriers limiting tree recruitment, but the relative magnitude of such barriers differs according to grass patch type. In two consecutive years (cohort 1 and 2) we sowed seeds and transplanted seedlings of Acacia in two grass patch types (prostrate/palatable and tussock/unpalatable grasses) in both, grazed and ungrazed plots. Each grass patch type was further manipulated to create three levels of grass competition (unclipped control, above-ground biomass removal and total biomass removal). Cattle grazing diminished seedling emergence of both cohorts and seedling survival of cohort 1. The effect of grass competition changed according to grass patch type. Prostrate grass cover enhanced emergence but lowered early survival, while tussock grass cover and also its total biomass removal facilitated early survival. During the second year, a severe drought drastically reduced Acacia recruitment, and it was strong enough to eliminate any grazing effects although the effect of grass competition on seedling establishment remained significant. Our results suggest that grazing and grass competition additively diminished the risk of woody establishment in this wet savanna. However, the stocking rate should be carefully balanced, thus contributing to the maintenance of a competitive grass cover to limit tree recruitment.